Impact of Rental Assistance on Modifiable Health Risk Factors and Behaviors in Adults - Antonakos, Cathy L. (Cityscape, 2018)
OBJECTIVES: Housing may influence health through various mechanisms and is recognized as a social determinant of health. This study investigated the influence of rental assistance on modifiable health risk factors and behaviors using data from the Panel Study of Income Dynamics (PSID). Participants receiving rental assistance were compared with participants not receiving rental assistance on body mass index (BMI), obesity, smoking, alcohol use and physical activity. METHODS: Participants (N=1374) were age 18 to 62, head of household, and had not received rental assistance for four years prior to baseline. Treatment group participants (N=116) received rental assistance between baseline and the two-year follow-up. Comparison group participants (N=1258) were eligible for rental assistance two years after baseline but did not receive assistance. Models estimated the average treatment effect on treated (ATET) for each health indicator in each follow-up year. Participants were matched on age, race-ethnicity, gender, education, disability status, employment, household income and number of children in the household. RESULTS: At the two-year follow-up, smoking was significantly higher among treatment group participants. A sensitivity analysis excluding permanently disabled participants showed significantly higher obesity in the treatment group two years after baseline. No significant differences were found four or six years after baseline on any outcome. CONCLUSIONS: Rental assistance was associated with increased smoking and obesity two years after baseline, but did not influence BMI, alcohol consumption, or physical activity. Interventions to reduce smoking and obesity may improve the health of individuals who receive rental assistance.